2015
DOI: 10.3390/cosmetics2020066
|View full text |Cite
|
Sign up to set email alerts
|

Topical Benefits of Two Fucoidan-Rich Extracts from Marine Macroalgae

Abstract: Abstract:Two concentrated and well-characterized fucoidan-rich extracts were investigated to determine their benefits in topical applications. An Undaria pinnatifida extract, containing 85% fucoidan, and a Fucus vesiculosus co-extract, containing 60% fucoidan and 30% polyphenol, were assessed in a number of in vitro assays to measure the effect of the extracts on enzyme inhibition, glycation, antioxidant activity and Sirtuin 1 (SIRT1) protein expression. Double-blind, placebo-controlled clinical studies were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 25 publications
2
61
1
2
Order By: Relevance
“…Fernando et al [142] concluded that brown algae sulfated polysaccharides have notable antioxidative and anti-inflammatory properties and are able to inhibit collagenase, elastase and tyrosinase therefore causing anti-wrinkling and skin-whitening effects. Brown algae extracts evaluated in the research of Fitton et al [143] positively affected skin protection, soothing and spot reduction.…”
Section: Brown Algae Sulfated Polysaccharides As Drug Delivery Systemmentioning
confidence: 95%
“…Fernando et al [142] concluded that brown algae sulfated polysaccharides have notable antioxidative and anti-inflammatory properties and are able to inhibit collagenase, elastase and tyrosinase therefore causing anti-wrinkling and skin-whitening effects. Brown algae extracts evaluated in the research of Fitton et al [143] positively affected skin protection, soothing and spot reduction.…”
Section: Brown Algae Sulfated Polysaccharides As Drug Delivery Systemmentioning
confidence: 95%
“…Double-blind clinical trials with fucoidan extracts show anti-aging effects on skin and other benefits in cosmetic applications (Fitton et al 2015). A common source of FCPs used in experimental studies is Fucus vesiculosus , but fucoidans also are found in edible species such as Cladosiphon okamuranus , Saccharina japonica ( as Laminaria japonica ), and Undaria pinnatifida (Fitton 2011).…”
Section: Polysaccharidesmentioning
confidence: 99%
“…This has been demonstrated successfully using several terrestrial plant extracts [137,138], but marine sources have received less attention. Recently, sulphated polysaccharide fucoidan was obtained from the phaeophyte Undaria pinnatifida and was shown to inhibit bacterial collagenase and human neutrophil elastase in vitro [139]. Additionally, a polyphenolic extract, containing fucoidan from the Figure 3 Approximate dry mass yields of collagen from different marine sources; fish skin and bone [127][128][129][130], cephalopods [134,135], echinoderm tests [131] and cnidarians [132,133].…”
Section: Collagenmentioning
confidence: 99%